Pharmacological therapy approaches for the treatment of knee osteoarthritis - Maren Hofmann; Pēteris Studers; Dārta Jakovicka (International Journal of Medical Research and Review, 2024)
To date, no effective treatment has been able to modify the pathological progression of osteoarthritis (OA). Current therapy can be broadly categorized into pharmacological and non-pharmacological approaches before considering surgical interventions. Non-pharmacological methods address lifestyle modifications, weight reduction and physical therapy, all aiming at alleviating mechanical stress on the affected joint. In this article, we focused on pharmacological treatment options, that primarily target pain reduction by reducing joint inflammation or restoring the altered synovial environment to a normal state. In this literature review, the main focus is on approved conservative therapies and examined emerging conservative strategies. Evaluating their advantages and limitations.